Multicomponent reactions (MCR) in medicinal chemistry: a patent review (2010-2020). (4th March 2021) - Younus, Hafiza Amna; Al-Rashida, Mariya; Hameed, Abdul; Uroos, Maliha; Salar, Uzma; Rana, Sobia; Khan, Khalid Mohammed
ABSTRACT: Introduction : Multicomponent reactions (MCR) has been utilized to synthesize a vast range of analogs belonging to diverse classes of heterocyclic compounds offering multidimensional pharmaceutical applications. The unique feature of MCR includes the synthesis of highly functionalized molecules in a single pot to build quick libraries of compounds of biological interest to identify new leads as potential therapeutic agents. Area covered : The current review article covers the patents published in the last decade in order to highlight the importance of multicomponent reactions for synthesizing complex-functionalized molecules of high biological significance. Expert opinion : Easily automated one-pot multicomponent reactions (MCRs) has demonstrated successful impact at different stages of the lead discovery, lead optimization, and pre-clinical process development arenas. Application of MCRs is the recent advancement in the field of drug design and discovery which will expectedly lead to the development of medicinally important heterocyclic compounds with a vast range of biological activities.